Equity by design: a rule-based framework for scholarship selection using the simple additive weighting method - Nurcahyo, Widyat; Auliamiliyani, Nur (Institute of Computer Science (IOCS), 2025)
This study presents the development of a decision support system designed to enhance the transparency and efficiency of scholarship recipient selection at Universitas Tama Jagakarsa. Utilizing the Simple Additive Weighting method, the system integrates key eligibility criteria—grade point average, parental income, and number of dependents—to compute preference scores that inform decision-making. The system was implemented using VB.NET and MySQL, following a waterfall model for development. Functional testing through black-box methods confirmed the system’s operational reliability, while user validation indicated strong acceptance and usability. Results demonstrate that the SAW algorithm effectively ranks applicants based on predefined weights and normalizations, offering a more objective and scalable alternative to manual selection processes. The system’s ability to process multi-criteria inputs and generate transparent, reproducible outcomes is a substantial contribution to scholarship administration in higher education. Findings suggest that integrating decision models into administrative processes can mitigate biases and improve institutional accountability. However, the study is limited by its focus on quantitative criteria and the use of a single decision-making algorithm. Future work should incorporate qualitative factors and assess alternative methods. The study affirms the potential of data-driven tools to support equitable access to educational opportunities, particularly for students from economically disadvantaged backgrounds.